2017
DOI: 10.1007/s10787-017-0344-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular effect of inflammation and nonsteroidal anti-inflammatory drugs on renin–angiotensin system in experimental arthritis

Abstract: A co-morbidity of inflammatory conditions is increased cardio-renal risks. Additionally, nonsteroidal anti-inflammatory drugs (NSAIDs) which are used to treat pain and inflammation are also associated with increase in such risks. We hypothesized that inflammation and NSAIDs impose the cardio-renal risk through the activation of the renin-angiotensin-system (RAS), a regulating pathway of the renal and cardiovascular homeostasis. We investigated the effect of adjuvant arthritis and NSAIDs on the RAS. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…In this study, Wistar rats that received exclusively meloxicam showed renal histological changes (basal membrane thickening and tubulointerstitial nephritis), which are in agreement with other studies [32][33][34] . On the other hand, rats that received meloxicam associated with nitrosyl ruthenium did not present such histological alterations and this is our main result.…”
Section: ■ Discussionsupporting
confidence: 93%
“…In this study, Wistar rats that received exclusively meloxicam showed renal histological changes (basal membrane thickening and tubulointerstitial nephritis), which are in agreement with other studies [32][33][34] . On the other hand, rats that received meloxicam associated with nitrosyl ruthenium did not present such histological alterations and this is our main result.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Examples of potential mechanisms of cardiac injury from COVID-19 include damage to the microvascular structure, ischemia from low oxygen availability, immune response-related inflammatory syndrome, and direct viral infection of the heart (11,(37)(38)(39)(40). From previous non-COVID-19 studies, it is known that inflammation can negatively affect cardiovascular health through actuating the reninangiotensin system (RAS) and thus disturbing the homeostasis of vasodilator and vasoconstrictor angiotensin peptides in the heart (41,42). Since both TnI and CK-MB are structural cardiac proteins, the severity of COVID-19 infection will determine the intensity of changes in these cardiac-specific markers.…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen, a commonly used NSAID and non-selective COX inhibitor, attenuates cardiac fibrosis and upregulates cardiac ACE2 expression in streptozotocin-induced diabetic rats ( Qiao et al, 2015 ). Other NSAIDs, including rofecoxib, meloxicam, celecoxib and flurbiprofen, at clinically relevant doses, were shown to induce modest increases in renal and cardiac ACE2 protein expression in adjuvant-induced arthritic rats ( Asghar, Aghazadeh-Habashi, & Jamali, 2017 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%